1988
DOI: 10.1037/0735-7044.102.4.534
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to morphine in the rat: Associative and nonassociative effects.

Abstract: Two experiments were conducted to examine the impact of dose level and interdose interval (IDI) on the development of tolerance to the analgesic effect of morphine. In Experiment 1, rats were administered a series of low- (5 mg/kg) or high- (30 mg/kg) dose injections of morphine either explicitly paired or unpaired with a distinctive context at a 48-hr IDI. The development of tolerance following this regimen was assessed by shifts in dose-response curves to the right when animals were tested on a tail-flick de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
40
1

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 49 publications
10
40
1
Order By: Relevance
“…From fifth day, the TFLs began to show a progressive decline until they were indistinguishable from the response of sham animals. This may be due to opioid tolerance, which is a characteristic effect of repeated administrations of opiates [Tiffany and Maude-Griffin, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…From fifth day, the TFLs began to show a progressive decline until they were indistinguishable from the response of sham animals. This may be due to opioid tolerance, which is a characteristic effect of repeated administrations of opiates [Tiffany and Maude-Griffin, 1988].…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that a purely pharmacological explanation of drug tolerance is inadequate (Siegel, 1975(Siegel, ,1976(Siegel, ,1977(Siegel, ,1988(Siegel, ,1989Tiffany & Maude-Griffin, 1988). Drug adaptation systems are modulated by a number of nonpharmacological events, including conditioning manipulations.…”
mentioning
confidence: 99%
“…Studies that have used a wide variety of response measures and drugs have found that the degree of tolerance observed following repeated drug administration is inversely related to IDI. For example, this relationship has been reported for the hypothermic response to ethanol (Stewart et al 1992), the anticonvulsant effect of clobazam (Wildin and Pleuvry 1992), the reduction of motor activity induced by haloperidol (Carey and De Veaugh-Geiss 1984), analgesia produced by morphine (Tiffany and Maude-Griffin 1988;Dafters and Odber 1989;Tiffany et al 1992), and some measures of subjective responses to nicotine (Perkins et al 1995).…”
Section: Introductionmentioning
confidence: 85%